Les éco-quartiers comme construction infrapolitique d’un habiter ? - Guillaume Faburel (Développement Durable et Territoires)
Sustainable neighborhoods became the first planning tools, particularly in France. However, after the time of eco-technological innovation and architectural purposes, their appropriation modes are now questioned. Linked to the projects timing, the issue of sustainable lifestyles arises. Combining three research conducted between 2009 and 2013, discourse analysis of stakeholders projects and, especially, empirical observation of four Swedish, German and Dutch sustainable neighborhoods, and, then, of three French inhabitants initiatives and / or social district (Tarn, Ille-et-Vilaine, Creuse) show that some of them would rise to new forms of individual and collective involvement and commitment, embedded in lifestyles, including development of specific value fields. Away from institutionalized participation tools, this infrapolitics involves particularly environmental issues and social transformation in and for the composition of new commons.